Пошаговое объяснение:
1.
1) - 2,1•3,8=-7,98
2) - 1• (-2) = 2
3) - 14,16: (-0,6) = 23,6
4) - 18,36:18=-1,02
2.
1) - 1,6x• (-5y) = 8xy
2) - 7a-9b+a+11b=-6a+2b
3) a - (a-8) + (12+a) = a-a+8+12+a=a+20
4) - 3 (c-5) + 6 (c+3) = - 3c+15+6c+18=3c+
33
3.
(-4,16 - (-2,56)) : 3,2-1,2• (-0,6) = - 1,6:3,2+
0,72=-0,5+0,72=0,22
4.
-2 (2,7x-1) - (6-3,4x) + 8 (0,4x-2) = - 5,4x+2
-6+3,4x+3,2x-16=1,2x-20
x=-1
1,2• (-1) - 20=-1,2-20=-21,2
5.
eсли 2 х-у=-8
у=2 х+8
-0,8x - (0,6x-0,7y) = - 0,8x-0,6x+0,7y=
-1,4x+0,7y=-1,4x+0,7• (2x+8) = - 1,4x+1,4x+5,6=5,6
9а+6а=а(9+6)
ответ: а(9+6)
а(9+6)=15а.